Corynebacterium pseudotuberculosis hos alpacka - Norgren, Tobias (2008)
The alpaca is a camelid that originate from the South American highland. During recent years it's been possible to keep alpacas in other parts of the world. Today there is a world-wide interest in alpacas, but there is still limited knowledge about this fascinating animal. There are approximately 350-400 alpacas in Sweden in 2007. In 2003 a Swedish alpaca herd was diagnosed with a Corynebacterium pseudotuberculosis infection and this caused considerable problems. The bacteria has a world-wide distribution and is a pathogen to most mammals, but mostly recognized as the causative agent of caseous lymphadenitis in sheep and goats. The disease is described in sheep and goats in Sweden, but present incidence is unclear. There are few scientific publications regarding C. pseudotuberculosis in alpacas, which has given some problems in the handling of C. pseudotuberculosis in Swedish alpacas. In this degree project there is a compilation of publications and practical experiences concerning alpacas. In these you can establish that this disease has the potential of causing great economic losses and suffering. The disease is primarily characterized by abscessation of the external lymphnodes and can be highly contagious, in some cases mortal. The bacteria has capabilities to withstand treatment and therefore it's difficult to eradicate. The disease can be controlled by treatment, isolation and surveillance. To eradicate the disease from a herd you need to segregate or cull infected animals.